An evidence-based method for targeting an abusive head trauma prevention media campaign and its evaluation. Issue 5 (November 2015) - Stewart, Tanya Charyk; Gilliland, Jason; Parry, Neil G.; Fraser, Douglas D.
Abstract : BACKGROUND: A triple-dose abusive head trauma (AHT) prevention program (Period of PURPLE Crying) was implemented. The third dose consisted of an education media campaign. The study objectives were to describe the qualitative and spatial methods developed to target AHT prevention and to evaluate this campaign. METHODS: A questionnaire on the level of importance of factors, rated on a 7-point Likert scale, was distributed to a panel of experts to determine the best advertising locations. Ranked factors were used to create weights for statistical modeling and mapping within a Geographic Information Systems to determine optimal ad locations. The media campaign was evaluated via a telephone survey of randomly selected households. RESULTS: The survey found locations of new families, high population density, and high percentage of lone parents to be the most important factors for selecting billboard sites. Spatial analysis revealed six areas that ranked highest in our factors. Five billboards, four media posters, and six transit shelters were selected for our advertisements. A population-based telephone survey revealed that 23% of respondents knew the campaign. Nearly half (42%) heard the radio public service announcements, and 9% saw billboards. CONCLUSION: Extending primary prevention efforts to the public helps to create a cultural change in the way inconsolable crying, the trigger for AHT, is viewed. With the use of ranked factors and Geographic Information Systems, geographic locations with high visibility and specific risk factors for AHT were identified for targeting the campaign, facilitating the likelihood that our message was reaching the population in greatest need.